Methods Of Improving The Quality Of Medical Education Through The Teaching Of Biochemistry, Adjusting Its Teaching And Assessment, And Introducing New Teaching Methods (Texas Journal of Medical Science, 2024)
This article examines strategies to enhance medical education by focusing on the teaching and assessment of biochemistry, acknowledging that effective pedagogy is crucial for elevating educational outcomes and impacting both mental and physical health. We propose a comprehensive framework that integrates traditional pedagogical approaches with Bloom's taxonomy, Cambridge methods, and 5E model, alongside interactive and adaptive learning technologies. By refining assessment methods and incorporating these innovative strategies, our aim is to improve student engagement, understanding, and practical application of biochemical knowledge in medical practice